Should Canadian Medical Schools Implement a Widespread 3 Year Medical Curriculum? (Canadian Medical Education Journal, 2010)
Background: This paper addresses the potential costs and benefits of implementing a widespread 3 year medical curriculum across the country.Methods: We compared differences in curriculum, costs, workforce production, competency, exposure to experiences, timing of career choices, and maturity of students and physicians between 3 and 4 year programs.  We accessed this information from 5 school’s online course outlines and by performing a broad search of the literature.Results- Three and four year medical programs have very similar curricular content.  The most significant cost savings in a 3 year medical program are due to these students entering the workforce a year earlier.   A 3 year program would add more physicians to our workforce initially; however, more doctors are produced over the long term by expanding class sizes.  Test scores of graduates from 3 year programs in Canada and the US are similar to graduates from 4 year medical programs.  A shorter program could limit the exposure of students to extra curriculars and force them to make earlier career decisions; however, time spent in electives appears to be similar.Conclusions: We do not find enough compelling evidence to advocate switching all medical schools in Canada to a 3 year medical program.